Implementasi Pelaporan Keuangan Berbasis Digital di Yayasan Radiyatan Mardiyah Prumpung Jakarta Timur - Lucyanda, Jurica; Widiastuti, Tuti; Santoso, Berkah Iman (LPkM Universitas Bakrie, 2021)
This service aims to provide training related to financial reporting of non-profit oriented entities (EBNL) to the Radiyatan Mardiyah Foundation (YRM), Prumpung Tengah, East Jakarta based on the digital-based Interpretation of Financial Accounting Standards (ISAK). The problems faced by the YRM as a non-profit oriented entity (EBNL) are the newly established foundation and the preparation of financial reports based on accounting standards that have been made by the Indonesian Institute of Accountants (IAI) according to the needs of each entity. The limited understanding of the Foundation's management related to internal/external communication and financial reporting based on certain standards is an important thing to be facilitated by providing internal/external communication training for organizational strengthening and preparation of financial reports based on ISAK 35. In addition, the demands for rapid technological development have become focus of this service activity is to facilitate foundation management to make digital-based reports, so that financial reports can be made easily. The method of training and socialization activities is carried out with an online system due to the Covid 19 pandemic conditions. Training activities are carried out with pre-test stages, presentation of training materials, discussions and questions and answers. The pre-test results concluded that the foundation management mostly understood the simple financial statements but did not understand ISAK 35. The training focuses on explaining financial statements based on SAK 35. Furthermore, after the training is carried out socialization of web-based financial statements. The socialization of digital-based financial reports based on ISAK 35 was carried out to explain to the management, especially the finance and accounting divisions so that they understand how to record all transactions using the system built. There is limited time of the service activity then the continuation of this activity is to conduct assistance in the form of monitoring and evaluations of implementation ISAK 35 in YRM.